(untitled) (Педагогіка вищої та середньої школи, 2007)
In the article an author examines the concept of reflection in philosophical, psychological, pedagogical aspects. Implementation of educational-creative works in the genre of self-portrait is shown as mean of development of reflection of future teachers of fine art.